Respons Psikologis terhadap Pandemi Covid-19 dalam Cerita Fantasi - Dwi Sastra Nurrokhma; Wahyudi Siswanto; Yuni Pratiwi (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study examines the psychological response to the Covid-19 pandemic in fantasy stories. This psychological response is reflected in the characterization of the characters in the fantasy story. The data of this research are narrative quotes, dialogue quotes, and fantasy story paragraphs that contain direct and indirect psychological responses. The data source of this research is a fantasy story with the theme of the Covid-19 pandemic written by grade VII students of MTsN Gresik. The theme of the fantasy story that was used as the data source was also determined, namely the Covid-19 pandemic. This theme is adapted to the circumstances experienced by students at this time. Data collection in this study was carried out in several steps. First, convey material related to understanding, structure, linguistic elements, and steps to writing fantasy stories to students. Second, assigning students to write fantasy stories according to predetermined themes. Third, observe and carefully read the fantasy stories written by students. Fourth, identify data and adjust it to the research focus. Fifth, code the data. Sixth, classify and describe the data. From the data analysis that has been done, several psychological responses were found. First, a cognitive response in the form of a character's knowledge of the Covid-19 pandemic. Second, affective responses related to the emotions of characters in the face of the Covid-19 pandemic. Third, a conative response in the form of actions taken by figures in the face of the Covid-19 pandemic.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan bentuk respons psikologis terhadap bencana pandemi Covid-19 dalam cerita fantasi. Respons psikologis ini tercermin pada penokohan tokoh dalam cerita fantasi tersebut. Data penelitian ini berupa kutipan narasi, kutipan dialog, dan paragraf cerita fantasi yang mengandung respons psikologis secara verbal. Sumber data penelitian ini adalah cerita fantasi bertema pandemi Covid-19 yang ditulis siswa kelas VII MTsN Gresik. Tema dari cerita fantasi yang dijadikan sumber data juga ditentukan yaitu pandemi Covid-19. Tema ini disesuaikan dengan keadaan yang dialami siswa pada masa ini. Pengumpulan data dalam penelitian ini dilakukan dengan beberapa langkah. Pertama, menyampaikan materi terkait pengertian, struktur, unsur kebahasaan, dan langkah-langkah penulisan cerita fantasi kepada siswa. Kedua, memberikan penugasan ke siswa untuk menulis cerita fantasi sesuai tema yang sudah ditentukan. Ketiga, mengamati dan membaca secara saksama cerita fantasi yang ditulis siswa. Keempat, mengidentifikasi data dan menyesuaikan dengan fokus penelitian. Kelima, memberi kode pada data. Keenam, mengklasifikasikan dan mendeskripsikan data. Dari analisis data yang telah dilakukan, ditemukan beberapa respons psikologis. Pertama, respons kognitif berupa pengetahuan tokoh terhadap pandemi Covid-19. Kedua, respons afektif yang berkaitan dengan emosi tokoh dalam menghadapi pandemi Covid-19. Ketiga, respons konatif berupa tindakan yang diambil tokoh dalam menghadapi pandemi Covid-19.